The relationship between brand coolness, brand love, loyalty and e-WOM: A text mining and sentiment analysis approach focused on a tech brand (Apple) - Apolinário, João Pedro de Sousa (2023)
Brand coolness is a multidimensional construct that encompasses different characteristics consumers perceive in a brand they think is cool. More research has been dedicated to the theme in recent years, been recognized as being of great importance for companies and marketeers alike. Brand love is another construct, which encompasses many kinds of positive emotions a customer can have regarding a brand. Previous research has been mostly based on prompted, pre-formatted surveys. Concurrently, the new wealth of data available online has brought along new technology able to extract and analyze said data, its value being widely recognized for many marketing and managerial purposes. This dissertation contributed to existing research by proposing a different method to gather and analyze consumer online feedback regarding a tech brand, using text mining and sentiment analysis techniques. More than 2000 consumer reviews were extracted, cleaned, processed and analyzed and a model was tested using linear regression models, for the relationship between brand coolness, brand love, loyalty and e-WOM (measured in its volume). Results showed brand coolness is rather present in consumer online feedback regarding a tech brand, and that of all the brand coolness subdimensions, useful/reliable, usability and aesthetic were the most represented; extraordinary, energetic, and original/innovative were the most positively evaluated. In addition, results also showed there is in fact a causation effect of brand coolness on brand love and of those two on loyalty. The causal relationship between brand love and loyalty with e-WOM, measured in its volume, was not statistically significant.